Different fingerprinting strategies to differentiate Porana sinensis and plants of Erycibe by high‐performance liquid chromatography with diode array detection, ultra high performance liquid chromatography with tandem quadrupole mass spectrometry, and chemometrics. Issue 2 (9th December 2014) - Chen, Zhiyong; Liao, Liping; Yang, Yuanyuan; Zhang, Zijia; Wang, Zhengtao
<x xml:space="preserve">Abstract</x> Plants of Erycibe are widely used in traditional Chinese medicine for the treatment of joint pain and rheumatoid arthritis. With the reduction of Erycibe resources in the wild, Porana sinensis has been widely used as a substitute. However, it is important to understand the chemical distinctions between the two kinds of plants and identify their individual chemical markers. In this study, multiwavelength chromatographic fingerprint and precursor ion fingerprint techniques were used in conjunction with chemometric tools to fingerprint and thus differentiate between plant samples. The similar results obtained from different fingerprints prove the reliability of the two fingerprints. Results obtained from principal component analysis and orthogonal projection to latent structures discriminant analysis identified similarities between the chemical components of P. sinensis and plants of Erycibe. However, concentrations of 4‐caffeoylquinic acid, 3, 5‐dicaffeoylquinic acid, 3, 4‐dicaffeoylquinic acid, and 4, 5‐dicaffeoylquinic acid were higher in P. sinensis than in plants of Erycibe, suggesting that P. sinensis may be more effective in medical treatments of some diseases than Erycibe.